2015
DOI: 10.1186/s12952-015-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic examination of brain volumetric abnormalities in recent-onset schizophrenia using voxel-based, surface-based and region-of-interest-based morphometric analyses

Abstract: BackgroundBrain morphometric abnormalities in schizophrenia have been extensively reported in the literature. Whole-brain volumetric reductions are almost universally reported by most studies irrespective of the characteristics of the samples studied (e.g., chronic/recent-onset; medicated/neuroleptic-naïve etc.). However, the same cannot be said of the reported regional morphometric abnormalities in schizophrenia. While certain regional morphometric abnormalities are more frequently reported than others, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Although most studies using VBM analysis have reported gray matter density reduction in patients in the early stages of schizophrenia, some researchers revealed no such results 45,46 . Our study corroborated the latter's finding and revealed no difference in gray matter density between the brain regions of patients diagnosed with schizophrenia for less than 5 years and those of the controls.…”
Section: Progression Of Brain Abnormalities Throughout the Illness Co...mentioning
confidence: 99%
“…Although most studies using VBM analysis have reported gray matter density reduction in patients in the early stages of schizophrenia, some researchers revealed no such results 45,46 . Our study corroborated the latter's finding and revealed no difference in gray matter density between the brain regions of patients diagnosed with schizophrenia for less than 5 years and those of the controls.…”
Section: Progression Of Brain Abnormalities Throughout the Illness Co...mentioning
confidence: 99%
“…However, there is no consensus on the most accurate way of the brain/head-size adjustment in statistical analyses (Arndt et al, 1991;Mathalon et al, 1993;O'Brien et al, 2006). Since TBV and ICV have their advantages and disadvantages (John et al, 2015), we decided to compare the regional brain volumes using both measures. The interactions and associations were studied in the GLM (General Linear Model) ANCOVA environment with TBV, ICV, age, sex as the co-variates and the sex-age interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these primary aims, we also sought to compare results from voxel‐based morphometry (VBM) and surface‐based morphometry (SBM), two common structural imaging techniques for assessing GM. These approaches are rarely compared in morphometry studies [John et al, ; Smolker et al, ]; however, both methods provide estimates of volume, albeit by using different calculations [relative proportion of GM in VBM, versus surface area by cortical thickness in SBM; Smolker et al, ] that may provide complementary information about underlying pathology. While VBM is useful as an overall index, SBM might provide more useful information for further investigation of underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%